A88 A PROSPECTIVE STUDY OF MECHANISMS OF INTESTINAL INFLAMMATION AFTER ILEAL RESECTION IN CROHN’S DISEASE: PRELIMINARY ANALYSIS OF PHENOTYPIC PREDICTORS OF ENDOSCOPIC RECURRENCE - Boland, K (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Post-operative endoscopic recurrence of ileal Crohn’s Disease (CD) is common, however the evolution of disease recurrence over time requires further analysis to identify mechanisms of intestinal inflammation. AIMS: The aim of this project is to study the complex interplay between genetic, microbial and gene expression as well as phenotypic features associated with post-operative ileal endoscopic recurrence. Here we present preliminary analysis of recruited subjects. METHODS: Patients with confirmed CD scheduled to undergo elective or emergent ileocolic resection with a primary anastomosis were recruited to this prospective study at a tertiary referral center. Clinical data, peripheral blood and serum collection was performed pre-operatively and at follow up for endoscopic assessment including activity scores and biopsies for microbiome analysis. Endoscopic recurrence was defined as Rutgeert’s score of i2, i3 or i4 in the neo-terminal ileum. RESULTS: Forty-five patients were enrolled in this study. Thirteen patients withdrew from the study, and 3 await first endoscopy post ileal resection. Twenty-nine patients have completed at least 1 post-operative endoscopy, and 27/29 completed 2 post-operative colonoscopies with a median follow-up interval of 18 months (4–144 months). Forty-one per cent (n=12/29) of patients developed endoscopic recurrence in the neo-terminal ileum. There were no statistically significant differences in age, gender, age at diagnosis, history of smoking or Montreal Classification of CD in patients with endoscopic recurrence. There was no significant difference in history of previous surgery for IBD in patients with recurrence (P=0.66). However, shorter time to first abdominal surgery for CD predicted endoscopic recurrence (median 1 versus 8 years, P=0.017, Mann Whitney Analysis). Use of disease-modifying medication at the time of ileal resection including systemic steroids, antibiotics, immunomodulators and anti-TNF agents did not predict endoscopic recurrence at post-operative colonoscopies. Treatment with anti-TNF at the time of the first post-operative colonoscopy was associated with survival without endoscopic disease recurrence (n=5/29, P=0.0388, Log-rank [Mantel Cox] Test). CONCLUSIONS: Preliminary phenotypic results of a prospective analysis of patients undergoing potentially curative resection for ileal CD demonstrate that a shorter time to first surgery for CD predicted endoscopic recurrence (P=0.017), indicating potentially more aggressive phenotype in these patients. Furthermore, use of anti-TNF post-operatively before colonoscopy assessment was also associated with a lower risk of endoscopic recurrence (P=0.388). These results will support ongoing investigation of the microbial and transcriptomic data to be evaluated in this group. FUNDING AGENCIES: NIH